การนำเสนอแนวทางการเสริมสร้างแรงจูงใจการปฏิบัติงานของครูในสถานศึกษาขนาดเล็ก สังกัดสำนักงานคณะกรรมการการศึกษาพื้นฐาน - ยอดเพชร, สมชาย; จันทร์บรรจง, ฉันทนา; มีแจ้ง, สำราญ; วรรณศรี, จิติมา (Journal of Education and Innovation, 2014)
บทคัดย่อ การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อ (1) ศึกษาความต้องการปัจจัยและกระบวนการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครูในสถานศึกษาขั้นพื้นฐานขนาดเล็ก (2) สร้างแนวทางการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครูในสถานศึกษาขั้นพื้นฐานขนาดเล็ก และ (3) การตรวจสอบแนวทางการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครูในสถานศึกษาขั้นพื้นฐานขนาดเล็ก วิธีดำเนินการวิจัย มีดังนี้ (1) การศึกษาความต้องการปัจจัยและกระบวนการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครูในสถานศึกษาขั้นพื้นฐานขนาดเล็ก โดยศึกษาจากกลุ่มตัวอย่างที่เป็นข้าราชการครูในสถานศึกษาขั้นพื้นฐานขนาดเล็ก จำนวน 371 คน คิดเป็นร้อยละ 92.75 ของกลุ่มตัวอย่าง ได้มาโดยการสุ่มตัวอย่างแบบหลายขั้นตอน เครื่องมือที่ใช้ในการวิจัยเป็นแบบประเมินค่า 5 ระดับ และวิเคราะห์ข้อมูลโดยวิธีหาค่าเฉลี่ย และค่าความเบี่ยงเบนมาตรฐาน (2) การสร้างแนวทางการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครูในสถานศึกษาขั้นพื้นฐานขนาดเล็ก การตรวจสอบความเหมาะสมและความเป็นไปได้ของแนวทางโดยใช้กระบวนการสนทนากลุ่มของผู้เชี่ยวชาญ 7คน และ (3) การตรวจสอบแนวทางการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครูในสถานศึกษาขั้นพื้นฐานขนาดเล็กเกี่ยวกับความเหมาะสมของแนวทาง โดยผู้บริหารสถานศึกษา 1 คน ครู 7 คน และผู้เชี่ยวชาญ 6 คน ผลการวิจัยปรากฏ ดังนี้ 1. ความต้องการปัจจัยและกระบวนการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครูในสถานศึกษาขั้นพื้นฐานขนาดเล็ก โดยรวมและทุกรายด้านอยู่ในระดับมาก 2. แนวทางการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครูในสถานศึกษาขั้นพื้นฐานขนาดเล็ก มี 2 แนวทางหลัก 5 แนวทางย่อย 2.1) แนวทางการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครูด้วยปัจจัยที่เป็นตัวเงิน ประกอบด้วย 2 แนวทางย่อย โดยมีวัตถุประสงค์ในการเสริมสร้างแรงจูงใจ 2 วัตถุประสงค์ 2 เป้าหมาย และ 7 วิธีการ 2.2) แนวทางการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครูด้วยปัจจัยที่ไม่ใช่ตัวเงิน ประกอบด้วย แนวทางย่อย 3 แนวทาง โดยมีวัตถุประสงค์ในการเสริมสร้างแรงจูงใจ 3 วัตถุประสงค์ 10 เป้าหมาย และ 73 วิธีการ 3. แนวทางการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครูในสถานศึกษาขั้นพื้นฐานขนาดเล็ก มีความเป็นไปได้ คำสำคัญ: แนวทาง/ เสริมสร้างแรงจูงใจ Abstract The purposes of this research were: (1) to study the needs of the factors and the procedures of the motivation enrichment of work performance among teachers in small-sized schools for basic education: (2) to develop the guidelines for motivation enrichment of work performance among teachers in small-sized schools for basic education and (3) to check the guideline for motivation enrichment of work performance among teachers in small-sized schools for basic education. The research methodologies were: (1) studying the needs of the factors and the procedure of the guideline for motivation enrichment of work performance among teachers in small-sized schools for basic education from 371 teachers. The response rate was 92.75% of the sample size (400 teachers). Data were collected from 5 rating scale questionnaires. The collected data were analyzed to obtain basic statistics of means and standard deviations : (2) developing the guideline for motivation enrichment of work performance among teachers in small-sized schools for basic education by nonparametric method, using focus group discussion from 7 educational experts to evaluate the appropriateness and (3) checking the guideline for motivation enrichment of work performance among teachers in small-sized schools for basic education by interviewing one school 1 director 7 teachers and 6 educational experts. The research result revealed as follows: 1. The needs of the factors and the procedure of the motivation enrichment of work performance among teachers in small-sized schools for basic education was at a high level as a whole and in all areas. 2. There are 2 main guidelines and 5 sub-guidelines of the guideline for motivation enrichment of work performance among teachers in small-sized schools for basic education 2.1 The monetary guidelines composed of 2 sub-guidelines, 2 aims, 2 purposes and 7 collective measures. 2.2 The non-monetary guidelines composed of 3 sub-guidelines, 3 aims, 10 purposes and 73 collective measures. 3. The guidelines for motivation enrichment of work performance among teachers in small-sized schools for basic education is feasible Key words: Guideline/ Motivation Enrichment